2008
DOI: 10.1088/1126-6708/2008/08/035
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogap and time reversal breaking in a holographic superconductor

Abstract: Classical SU (2) Yang-Mills theory in 3+1 dimensional anti-de Sitter space is known to provide a holographic dual to a 2+1 system that undergoes a superconducting phase transition. We study the electrical conductivity and spectral density of an isotropic superconducting phase. We show that the theory exhibits a pseudogap at low temperatures and a nonzero Hall conductivity. The Hall conductivity is possible because of spontaneous breaking of time reversal symmetry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 45 publications
(92 reference statements)
10
141
0
Order By: Relevance
“…It was also numerically shown that the scalar field condensation occurs below a critical temperature under the presence of an external magnetic field [8,9,10]. Quite recently, general properties of p-wave superconductors were investigated by Gubser and Pufu [11] and independently by Roberts and Hartnoll [12] in a model of a non-Abelian gauge field in the background of AdS 4 -Schwarzschild black hole.…”
Section: Introductionmentioning
confidence: 99%
“…It was also numerically shown that the scalar field condensation occurs below a critical temperature under the presence of an external magnetic field [8,9,10]. Quite recently, general properties of p-wave superconductors were investigated by Gubser and Pufu [11] and independently by Roberts and Hartnoll [12] in a model of a non-Abelian gauge field in the background of AdS 4 -Schwarzschild black hole.…”
Section: Introductionmentioning
confidence: 99%
“…We have found this kind of behavior in our system in the anisotropic case, finding condensed solutions and constructing the phase diagram. Second, we compute free energies and find that for any set of values of the free parameters that determines the solutions, the anisotropic phase is energetically favored over the isotropic phase, as conjectured in other contexts [29][30][31]. Third, we analyze the zero temperature limit, case that had not been addressed before; for low enough gravitational coupling we find solutions which spontaneously break the U(1) symmetry and have zero entropy, and so describe the true ground state of the system.…”
Section: Jhep07(2015)172mentioning
confidence: 80%
“…Our discussion of the time-reversal breaking holographic superconductor [20] follows the conventions of [25]. Let us consider the following action:…”
Section: Setup and Solutionsmentioning
confidence: 99%